Synthesis of Both Enantiomers of the Streptomyces Alkaloid 4-epi-SS20846A - Scarpi, Dina; Avataneo, Ottavia; Prandi, Cristina; Venturello, Paolo; Occhiato, Ernesto G. (Synthesis, 2012)
The enantiodivergent synthesis of the Streptomyces alkaloid 4-epi-SS20846A was based on a Takai olefination/Suzuki–Miyaura coupling sequence for the highly stereoselective introduction of the E,E-pentadienyl side chain on the piperidine skeleton. Optical separation of a key hydroxylated enamide ester, prepared by palladium-catalyzed methoxycarbonylation of a lactam-derived enol phosphate, was successfully achieved by both lipase-catalyzed kinetic resolution and semipreparative HPLC. This approach allowed us to obtain the enantiopure target alkaloid in 35–38% yield over six steps.
Keywords: alkaloids; lactams; carbonylation; olefination; cross-coupling